PS 17-22 SIX MONTHS EXERCISE INTERVENTION SIGNIFICANTLY IMPROVES ALBUMIN-CREATININE RATIO IN PATIENTS WITH TYPE 2 DIABETES: A RANDOMISED CONTROLLED TRIAL. (September 2016) - Picone, Dean; Callisaya, Michele; Srikanth, Velandai; Schultz, Martin; Yang, Hong; Nolan, Mark; Greenaway, Tim; Sharman, James
Abstract : Objective: Patients with type 2 diabetes (T2DM) are at increased risk of elevated albumin creatinine ratio (ACR), a marker of kidney damage. Cross-sectional data suggests an inverse relationship between ACR and physical activity, however it is unclear whether a structured exercise intervention can improve ACR in patients with T2DM. We sought to test this in the current study. Design and method: Fifty previously sedentary patients with T2DM (aged 55–75 years) were randomised to a six-month structured aerobic and resistance exercise program (n = 26, mean age 65 ± 5 years, 63% male) or control (n = 24, 67 ± 5 years, 42% male). Measurements taken pre- and post-intervention included: ACR (using standard laboratory techniques); aortic stiffness, clinic BP, 24-hour ambulatory (24-ABPM); and cardiorespiratory fitness via gas analysis (VO2 peak) during Bruce protocol treadmill testing. Results: There were no differences between groups at baseline for any measured variable. Compared with controls, there was a significant reduction in ACR (−0.9 ± 1.6 versus 0.6 ± 1.5, p = 0.011) with exercise intervention. However, there was no between group difference for the change in aortic stiffness, clinic BP or 24-ABPM. Exercise intervention significantly increased time on treadmill (85 ± 97 versus 17 ± 69 s, p = 0.018) and achieved borderline improvements in weight (−0.5 ± 2.5 versus 1.0 ± 2.1 kg, p = 0.051) and VO2 peak (0.9 ± 2.5 versus -0.7 ± 4.3 ml/min/kg, p = 0.21). The change in ACR with intervention remained significant after multiple adjustment including sex, weight, aortic stiffness, clinic BP, 24-ABPM or baseline ACR (p < 0.05). Conclusions: A six-month exercise intervention program significantly improved ACR in patients with T2DM, independent of BP and other variables associated with kidney function. Regular exercise should be advocated for kidney health in patients with T2DM.